The Influence of Balanced Nutrition Education on The Knowledge of Posyandu Cadres in Preventing Stunting - Maria Vilastry Nuhan; Damita Palalangan; Yosefa S.Atok; Christina R.Nenotek (Journal of Ners and Midwifery, 2023)
Childhood stunting, a persistent public health concern in Indonesia, has significant implications for long-term health. Improving the knowledge of balanced nutrition among Posyandu cadres plays a pivotal role in tackling this issue. Our objective was to assess the impact of balanced nutrition education on Posyandu cadre knowledge concerning stunting prevention. The research involved 129 participants and evaluated their knowledge through pretest and posttest scores, employing the Wilcoxon Sign Rank Test for statistical analysis. The results indicated that the majority of respondents initially possessed "sufficient" and "good" knowledge levels. However, following the educational intervention, a remarkable 69.8% achieved "good" knowledge, with a minimal 0.8% showing "insufficient" knowledge. The statistical analysis further revealed a significant disparity between pretest and posttest knowledge scores, underscoring the substantial and beneficial impact of balanced nutrition education. In conclusion, this research confirms the positive influence of nutrition education on Posyandu cadre knowledge. The findings emphasize the urgency of sustained, accessible nutritional education programs supported by government and healthcare institutions. Such efforts are imperative for effective stunting prevention, especially in high-stunting regions like East Nusa Tenggara.